Across the causeway a multi-dimensional study of Malaysia-Singapore relations - Shiraishi, Takashi (Institute of Southeast Asian Studies, 2009)
This book considers Malaysia-Singapore relations from a range of disciplinary perspectives. Geographical proximity, historical linkages, material flows, and movements have long connected the peoples and territories of Malaysia and Singapore in various ways and with varying degrees of intensity. Relations between the two countries have been shaped not only by competing visions of the nation and the different trajectories taken by these countries' nation-building projects, but also by the reality of economic interdependence and competition, security cooperation, and increasing embeddedness in the market-created East Asian region. The thirteen essays on history, politics, regional security, law, and economy collectively aim at a multi-dimensional study that seeks to convey the density and complexity of connections 'across the Causeway'.